2021
DOI: 10.1002/rmv.2213
|View full text |Cite
|
Sign up to set email alerts
|

Potential detrimental role of soluble ACE2 in severe COVID‐19 comorbid patients

Abstract: Summary Severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) enters the host cell by binding to angiotensin‐converting enzyme 2 (ACE2) receptor. Other important proteins involved in this process include disintegrin and metalloproteinase domain‐containing protein 17 (ADAM17) also known as tumour necrosis factor‐α‐converting enzyme and transmembrane serine protease 2. ACE2 converts angiotensin II (Ang II) to angiotensin (1–7), to balance the renin angiotensin system. Membrane‐bound ACE2 ectodo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
40
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(52 citation statements)
references
References 94 publications
2
40
0
Order By: Relevance
“…The therapeutic value of sACE2 has been suggested to exert a dual effect; a reduction in the levels of the vasoconstrictor angiotensin II, and blocking viral entry by masking the spike protein. However, in our cohort, as in other studies, severely ill patients, despite having high sACE2 levels, did not seem to gain a benefit in viral infection [34]. It has been proposed that a possible detrimental role of high sACE2 could be due to the binding of the virus to many sACE2 molecules; the virus-sACE2 complex can spread the virus to distant organs and create sACE2 and membrane ACE2 depletion.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…The therapeutic value of sACE2 has been suggested to exert a dual effect; a reduction in the levels of the vasoconstrictor angiotensin II, and blocking viral entry by masking the spike protein. However, in our cohort, as in other studies, severely ill patients, despite having high sACE2 levels, did not seem to gain a benefit in viral infection [34]. It has been proposed that a possible detrimental role of high sACE2 could be due to the binding of the virus to many sACE2 molecules; the virus-sACE2 complex can spread the virus to distant organs and create sACE2 and membrane ACE2 depletion.…”
Section: Discussionsupporting
confidence: 52%
“…It has been proposed that a possible detrimental role of high sACE2 could be due to the binding of the virus to many sACE2 molecules; the virus-sACE2 complex can spread the virus to distant organs and create sACE2 and membrane ACE2 depletion. The resulting increased angiotensin II, part of the bigger pathology, might aggravate the disease [34]. It is thus of utmost importance to monitor both sACE2 and angiotensin II levels in COVID-19 patients to ensure the safe and efficient use of therapeutic sACE2.…”
Section: Discussionmentioning
confidence: 99%
“…The sACE-2 is derived by shedding from the membranes due to the hydrolyzing activity of a membrane-anchored metalloproteinase 17 (ADAM17; Patel et al, 2014). ADAM17, involved in proinflammatory processes in epithelial and endothelial cells, is increased in several pathologies, including cardiopulmonary, and renal systems and gastrointestinal inflammatory diseases such as ulcerative colitis (Rahman et al, 2021). ACE-2 deficiency due to SARS-CoV-2 binding to the ACE-2 receptor, activates ADAM-17 (Andring et al, 2020).…”
Section: Ace-2 Distribution; Local Ace-2 Activity In the Respiratory And Gastrointestinal Tractmentioning
confidence: 99%
“…However, this soluble sACE-2 could act as a decoy to bind the virus and decrease the likelihood of viral binding to membrane-bound ACE-2. It has been recently suggested that the sACE-2 retains catalytic activity and that the sACE-2-virus complex could interact with TMPRSS2 and thus contribute to infection (Rahman et al, 2021). Increased sACE2 activity was observed in patients with heart failure (Epelman et al, 2008).…”
Section: Raas Inhibitors: Aceis and Arbs Do Not Address The Local Gut Ace-2 Deficiencymentioning
confidence: 99%
“…However, the plasma RAS balance in COVID-19 patients was already characterized by a strong transient increase in circulating plasma sACE2 [66]. Therefore, in COVID-19 patients with comorbid diseases, both Angiotensin II and virus adversely affect the prognosis by affecting the RAS balance in a way that down-regulates ACE2 [96]. Interestingly, recent study reports encouraging results in the first severe COVID-19 patient treated with hrsACE2 [97].…”
Section: Novel Treatment Options Targeting Defective Efferocytosis In Covid-19mentioning
confidence: 99%